PENGARUH KEGIATAN PRAKTIK DI LABORATORIUM PEMASARAN â€œMINI MARKET TANIAâ€ TERHADAP SOFT SKILLS MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS SEBELAS MARET - -, Dian Retno Fitriyani -; -, Leny Noviani -; -, Jonet Ariyanto Nugroho - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2016)
The research is aimed to know whether practical activities in marketing laboratory Tania Mini Market affects the students? soft skills of Economic Education of Sebelas Maret University Surakarta. This research quantitative research with descriptive methods. The population and sample in this research is the students of Economics Education, Teachers Training and Education Faculty of Sebelas Maret Surakarta class of 2012 and 2013. The technique to determine the sampling used is proportional random sampling. The technique to collect the data is by using questionnaire. The try out was done by using the activity outside of the chosen sample which were coming from students of Economics Education of Sebelas Maret Surakarta class of 2012 and 2013. The result of data validity in the questionnaire of the practice activities in marketing laboratory